Familial legacies: A study on Gujarati women and family entrepreneurship - Ranjana Singh; Tania Sebastian (Journal of Global Entrepreneurship Research, 2018)
Among the states of India, the State of Gujarat in India presents numerous opportunities for entrepreneurship. This is the result of entrepreneurship ingrained in the culture and tradition of Gujarat. The significant aspect examined in this article is the link between family and women entrepreneurs in Gujarat. Evidences has been gathered from six cities of Gujarat covering Northern, Eastern, Southern, Western and Central zones to portray the overall picture of Gujarat. The findings from the evidence is to be further explored and utilized for the betterment and upliftment of women entrepreneurs in India, as women lose out on self-sufficient job opportunities because of the traditional practice of disallowing women to work outside their homes and with strangers. Entrepreneurship, with the existing support and promotional measures in training and retaining skills in becoming an entrepreneur can go a long way for the nation and empowering women.
Keywords: 650; Women entrepreneurship; Family entrepreneurship; Financial problem; Technological problem; Succession; India; Gujarat